After Thirty Years, We Still Cannot Understand Why Methylene Blue is not a Reference to Treat Vasoplegic Syndrome in Cardiac Surgery - Evora,Paulo Roberto B. (2021)
Abstract Vasoplegic syndrome (VS) comprises a constellation of concurrent signs and symptoms: hypotension, high cardiac index, low systemic vascular resistance, low filling pressures, the tendency to occur diffuse bleeding, and sustained hypotension. All of these parameters may persist even despite the use of high doses of vasoconstrictor amines. VS arises from vasoplegic endothelial dysfunction with excessive release of nitric oxide by polymorphonuclear leukocytes mediated by the nitric oxide synthase’s inducible form and is associated with systemic inflammatory reaction and high morbimortality. The achievements regarding the treatment of VS with methylene blue (MB) are a valuable Brazilian contribution to cardiac surgery. The present text review was designed to deliver the accumulated knowledge in the past ten years of employing MB to treat VS after cardiac surgery. Considering that we have already published two papers describing acquired experiences and concepts after 15 and 20 years, now, as we achieve the 30-year mark, we compose a trilogy.